Asuhan Keperawatan Pada Pasien Hipertensi Dengan Nyeri Kepala Menggunakan Foot Massage Dan Progresive Muscle Relaxation - Ridawati, Indah Dewi; Febrianti, Rizky Alda (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Hypertension is a silent killer, since it lacks noticeable symptoms and definitive indicators of its presence. The therapy of hypertension involves both pharmaceutical and non-pharmacological approaches. Complementary therapy, such as Foot Massage and Progressive Muscle Relaxation, may be used as a non-pharmacological treatment for hypertensive patients. This therapy has the potential to enhance blood circulation, alleviate muscular tension, mitigate stress, and decrease blood pressure. Methods: The research used a descriptive methodology using a case study technique, with a sample size of 2 participants who were diagnosed with hypertension. This study was carried out over a period of 30 minutes, during which the researchers made three visits to participants' homes., Results: Following the implementation of Foot Massage and Progressive Muscle Relaxation techniques to alleviate pain in individuals with hypertension, a reduction in pain intensity was observed. Subject I initially reported a pain level of 6 on the pain scale, which decreased to 3 after the application of Foot Massage and Progressive Muscle Relaxation. Similarly, subject II experienced a decrease in pain from a level of 5 to 2 after receiving the same treatments. Conclusion: Utilising Foot Massage and Progressive Muscle Relaxation techniques may progressively enhance blood circulation and alleviate pain levels